Peran Guru dalam Pengelolaan Kelas untuk Meningkatkan Keaktifan Belajar Siswa pada Mata Pelajaran Akidah Akhlak di MTsN 2 Agam - Padilah Pajriani; Fenny Ayu Monia (Lembaga Yasin AlSys, 2026)
Although the role of teachers in classroom management to increase students’ learning engagement in Akidah Akhlak has been widely examined, research specifically addressing its implementation in the context of madrasah tsanawiyah, along with its supporting and inhibiting factors, remains limited. This study aimed to describe the role of teachers in classroom management to increase students’ learning engagement in Akidah Akhlak at MTsN 2 Agam and to identify the supporting and inhibiting factors in its implementation. This study employed a qualitative approach with a case study design through field research. The research informants consisted of the Akidah Akhlak teacher as the primary informant, the Vice Principal for Curriculum Affairs, and several students selected using purposive sampling. Data were collected through interviews, observations, and documentation and were subsequently analysed using the interactive model of Miles, Huberman, and Saldaña, which comprises data reduction, data presentation, and conclusion drawing. The results showed that the teacher performed the roles of facilitator, motivator, mentor, classroom manager, and evaluator in creating a conducive learning environment and encouraging students’ active participation. Successful classroom management was supported by teacher competence, students’ learning motivation, and the availability of learning facilities. Meanwhile, students’ low self-confidence, differences in academic ability, and lack of learning motivation constituted inhibiting factors. This study confirms that optimizing the teacher’s role in classroom management contributes to the creation of active, conducive, and student-centred Akidah Akhlak learning. These findings strengthen the literature on classroom management in Islamic Religious Education and provide practical implications for teachers and madrasahs in developing learning strategies that are more participatory and responsive to students’ characteristics.